Pengaruh Arus Kas Terhadap Tingkat Likuiditas Pt. Mayora Indah Tbk - Iin Ratnasari; Firli Agusetiawan Shavab (FEB Universitas Sultan Ageng Tirtayasa, 2016)
This study aims to determine the cash flow and liquidity in PT. Mayora Indah Tbk, also to determine how much incluence the cash flow liquidity PT. Mayora Indah tbk. The method used is descriptive method associative then prossesed and analyzed to infer. From the test results it can be seen that there is a strong relationship between the liquidity of cash flows because those cash flows are able to explain the changes in the liquidity of 77,8% and the remaining 22,2% influenced by other factors in addition to cash flow.The conclusion that can be drawn from this study is the cash flow and liquidity in PT. Mayora Indah Tbk, for four years of fluctuations. The suggestion that the author gave the compay should be able to manage the current assets of the company are better. Thus the company is always in liquid state so the state of company’s liquidity levels will be in a safe position.